Guillain-Barré Syndrome Outbreak Associated With Zika Virus Infection in French Polynesia: A Case-Control Study. Issue 8 (August 2016) - Cao-Lormeau, Van-Mai; Blake, Alexandre; Mons, Sandrine; Lastère, Stéphane; Roche, Claudine; Vanhomwegen, Jessica; Dub, Timothée; Baudouin, Laure; Teissier, Anita; Larre, Philippe; Vial, Anne-Laure; Decam, Christophe; et al.
Abstract : (Abstracted from Lancet 2016;387:1531–1539) French Polynesia suffered one of the largest outbreaks of the Zika virus between October 2013 and April 2014 with over 32, 000 patients being assessed for the infection. A few studies have reported a simultaneous occurrence of Zika virus and Guillain-Barré syndrome outbreaks in French Polynesia and Brazil, suggesting an association between the 2.